Effect of footrest on muscle activities during prolonged standing among workers in selected factories in Malaysia - Abdul Aziz, Adriana (2019)
Prolonged standing has been identified as one of the risk factors which associated with occupational injuries. The workers tend to suffer from Musculoskeletal Disorders (MSDs) after a chronic exposure of prolonged standing while performing their task. Such disorders can cause performance decrement and high rate of absenteeism among the workers. Therefore, ergonomic intervention such as footrest could be used, in order to reduce the muscle activity among workers. The main objective for this study is to determine the effect of footrest on muscle activity during prolonged standing activity. A total of 74 workers chosen from the Assembly Line from selected factory were divided into control (without footrest) and experimental (with footrest) group. The response rate obtained was 100% for this research. The respondents were required to perform the given task while standing for two hours continuously. The perceived exertion rating in both groups was evaluated (for every 15 minutes) by using Borg’s Scale CR-10 Questionnaire. Meanwhile, surface electromyography (sEMG) was used to monitor the muscle activity (right and left of the lower leg around calf area) specifically at tibialis and gastrocnemius muscles in both control and experimental groups throughout the experimental durations. The average of perceived exertion rating indicated by control group (0.07) was higher than experimental group (0.04) throughout the 2 hours session of prolonged standing for neck/head, shoulder, upper back, hands, lower back, buttocks, thighs, knees, calves and feet. However, these rating did not exceed more than 5. The results of statistical analysis has shown that perceived exertion rating on the lower body regions (lower back, knees, calves and feet) was significantly (p<0.05) more affected by prolonged standing compared to the upper body regions (neck/head, shoulder, upper back and hands) during the two hours period for both groups. The average of reduction of surface electromyography (sEMG) levels for both right and left tibilais anterior muscles and gastrocnemius posterior muscles respectively were 0.02 in experimental group when compared to the control group. There were statistically significant differences in the sEMG levels between control and experimental groups for both in the right and left studied muscles at the 60th minute within the experimental session. There was reduction of perceived exertion rating when assessed by using Borg’s Scale CR-10 and level of surface electromyography in experimental group than the control group. The intervention of footrest provides internal mechanism which reduces the muscle activity on body parts. This concluded that it was significant to state that footrest is success ergonomics’ intervention in terms of minimizing muscle activity in a prolonged standing work posture.